Unconventional formation of a 1D-chain of H-bonded water molecules in bipyridine-based supramolecular hexameric hosts of isostructural coordination compounds of Co(II) and Zn(II): Antiproliferative evaluation and theoretical studies. (15th November 2020) - Chetry, Sanjib; Sharma, Pranay; Frontera, Antonio; Dutta, Debajit; Verma, Akalesh K.; Bhattacharyya, Manjit K.
Graphical abstract: Antiproliferative activities considering cytotoxicity, apoptosis, molecular docking and pharmacophore features have been explored in isostructural Co(II) and Zn(II) compounds involving 1D hydrogen bonded (H2 O)8 chains enclathrated in supramolecular hexameric hosts. Highlights: Bipyridine based isostructural coordination compounds of Co(II) and Zn(II). Unconventional 1D (H2 O)8 chain in supramolecular hexameric hosts. Energetically significant anti-parallel π-stacking interactions. DFT calculations and NCI plot computational tools. Antiproliferative evaluation considering cytotoxicity, apoptosis and molecular docking. Significant pharmacophore features responsible for antiproliferative activities. Abstract: Two new isostructural coordination compounds of cobalt(II) and zinc(II) involving 2, 2′-bipyridine and 2, 5-pyridine dicarboxylate, viz . [Co(2, 5-PDC)(bipy)2 ]·7H2 O (1 ) and [Zn(2, 5-PDC)(bipy)2 ]·7H2 O (2 ) (bipy = 2, 2′-bipyridine and 2, 5-PDC = 2, 5-pyridine dicarboxylate), have been synthesized in purely aqueous medium at room temperature. The compounds have been further characterized by single crystal X-ray diffraction, FT-IR, electronic spectroscopy, thermal and elemental analysis. Several non-covalent interactions, such as CH⋯O and anti-parallel π-stacking contacts, build up the supramolecular layered architectures of the crystal structures. Further analysis of the crystal structures reveals the self-assembled enclathration of a 1D H-bonded (H2 O)8 chain into the supramolecular hexameric host cavity which brings rigidity to the crystal structures. Such unconventional enclathration of H-bonded water molecules in a metal–organic supramolecular host involving bipy is scarcely described in the literature. We have theoretically evaluated the strength of the anti-parallel π-stacking interactions that are crucial for the stabilization of the supramolecular dimers of the compounds. The influences of the metal coordination on the strength of the π-stacking interactions have been confirmed using DFT calculations and NCI plot computational tools. The antiproliferative activities of the compounds have been investigated in the DL cell line using MTT cell viability and apoptosis assays. The compounds significantly induce concentration dependent cell cytotoxicity and apoptosis in DL cells with negligible cytotoxicity in normal (PBMC) cells. A molecular docking study also reveals a strong interaction of the compounds with the active site of anti-apoptotic BCL proteins. Pharmacophore features of the structures of the compounds responsible for the biological activities were also generated to establish a structure activity relationship (SAR).